DESIGN OF DIGITAL NEWA PELAMINAN CATALOG IN PADANG CITY - NEWAHYU JAMALIKA SHINTIA, Drs. Ariusmedi, M.Sn. Dra. Zubaidah, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The city of Padang is the capital of the province of West Sumatra. As a provincial city there are many businesses engaged in services, among the service bureaus in the city of Padang are Newa pelaminan. Newa Pelaminan has been established for 13 years but the promotion carried out has not gone well. Presentation of information about products in Newa Pelaminan is still not well presented.The purpose of this design is to produce a digital catalog of Newa Pelaminan in Padang that is attractively packaged with photos of products from Newa Pelaminan and contains information about contact persons, addresses, and websites that are expected to provide information to clients to contact or visit stores from Newa Aisle.The data analysis method used is SWOT (Strength, Weakness, Opportunity, Threat). Data collection begins with observation, interviews and documentation. The design of this digital catalog uses photos of products from Newa Pelaminan, text, colors and layouts that are interesting and understandable. Through the design of this catalog, it is hoped that the Newa Pelaminan business can attract the attention of the consumer audience so that in the future it can reach a wider target market. This design uses the theory of visual communication design, media, color, typography, and layout.This design produces a digital-based catalog containing price packages according to the price determined by the owner. Besides that, it also has a model of wedding, catering, fabric models, balloon, photographer and professional tents. Besides the main media, it is also equipped with several supporting media such as business cards, banners, children's doll hangers, signpost, x-banner, website, and social media.Keywords: Catalog Digital, Newa Pelaminan, Pelaminan in Padang City.